KONSEP AJARAN KAWRUH JIWA KI AGENG SURYOMENTARAM DALAM PSYCHOLOGICAL WELL-BEING (KAJIAN KONSELING LINTAS BUDAYA) - Khotibul Umam, Bagus; Ersta Kusumaningtyas, Lydia; Jawandi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Happiness is a universal human goal, gut its meaning is often distorted by material and ego constructs in the modern era. Amidst the dominance of Western counseling methods, integrating indigenous wisdom-based approaches like Kawruh Jiwa serves as a crucial alternative in guidance and counseling, particularly in cross-cultural contexts. This study aims to fundamentally re-examine the teachings of Kawruh Jiwa, specifically Kawruh Begja (the science of happiness) by Ki Ageng Suryomentaram, and evaluate its functional relevance to the concept of Psychological Well-Being (PWB). This research employs a qualitative approach using library research methods. Data collection was conducted through a litetrature study of primary and secondary sources, validated via researcher triangulation. Data were analyzed using content analysis to derive valid formulations. The results reveal that Kawruh Jiwa (specifically Kawruh Begja) and Psychological Well-Being share a functional convergence in constructing genuine happiness. The hallmark of Kawruh Begja lies in its applicative-contemplative dimension through the concept of nyawang karep (monitoring desires) to achieve a liberated soul (jiwa kramadangsa). On the other hand, PWB offers a multi-dimensioanl, empirically constructive framework. The integration of these two concepts provides a robust new theoretical foundation for pracitioners to develop cross-cultural and indigenous counseling practices in Indonesia.